Piloting a livestock identification and traceability system in the northern Tanzania–Narok–Nairobi trade route - Mutua, Florence K.; Kihara, Absolomon; Rogena, J.; Ngwili, N.; Aboge, G.; Wabacha, J.; Bett, Bernard K. (Springer, 2018)
We designed and piloted a livestock identification and traceability system (LITS) along the Northern Tanzania–Narok–Nairobi beef value chain. Animals were randomly selected and identified at the primary markets using uniquely coded ear tags. Data on identification, ownership, source (village), and the site of recruitment (primary market) were collected and posted to an online database. Similar data were collected in all the markets where tagged animals passed through until they got to defined slaughterhouses. Meat samples were collected during slaughter and later analyzed for tetracycline and diminazene residues using high-performance liquid chromatography (HPLC). Follow up surveys were done to assess the pilot system. The database captured a total of 4260 records from 741 cattle. Cattle recruited in the primary markets in Narok (n = 1698) either came from farms (43.8%), local markets (37.7%), or from markets in Tanzania (18.5%). Soit Sambu market was the main source of animals entering the market from Tanzania (54%; n = 370). Most tagged cattle (72%, n = 197) were slaughtered at the Ewaso Ng’iro slaughterhouse in Narok. Lesions observed (5%; n = 192) were related to either hydatidosis or fascioliasis. The mean diminazene aceturate residue level was 320.78 ± 193.48 ppb. We used the traceability system to identify sources of animals with observable high drug residue levels in tissues. Based on the findings from this study, we discuss opportunities for LITS—as a tool for surveillance for both animal health and food safety, and outline challenges of its deployment in a local beef value chain—such as limited incentives for uptake.